Correlation Between Early Plasma Interleukin 37 Responses With Low Inflammatory Cytokine Levels and Benign Clinical Outcomes in Severe Acute Respiratory Syndrome Coronavirus 2 Infection. (17th November 2020) - Li, Ang; Ling, Yun; Song, Zhigang; Cheng, Xiaobo; Ding, Longfei; Jiang, Rendi; Fu, Weihui; Liu, Yan; Hu, Huiliang; Yuan, Songhua; Chen, Jian; Zhu, Cuisong; et al.
Abstract: Background: The immune protective mechanisms during severe acute respiratory syndrome coronavirus (SARS-CoV-2) infection remain to be deciphered for the development of an effective intervention approach. Methods: We examined early responses of interleukin 37 (IL-37), a powerful anti-inflammatory cytokine, in 254 SARS-CoV-2–infected patients before any clinical intervention and determined its correlation with clinical prognosis. Results: Our results demonstrated that SARS-CoV-2 infection causes elevation of plasma IL-37. Higher early IL-37 responses were correlated with earlier viral RNA negative conversion, chest computed tomographic improvement, and cough relief, consequently resulted in earlier hospital discharge. Further assays showed that higher IL-37 was associated with lower interleukin 6 and interleukin 8 (IL-8) and higher interferon α responses and facilitated biochemical homeostasis. Low IL-37 responses predicted severe clinical prognosis in combination with IL-8 and C-reactive protein. In addition, we observed that IL-37 administration was able to attenuate lung inflammation and alleviate respiratory tissue damage in human angiotensin-converting enzyme 2–transgenic mice infected with SARS-CoV-2. Conclusions: Overall, we found that IL-37 plays a protective role by antagonizing inflammatory responses while retaining type I interferon, thereby maintaining the functionalities of vital organs. IL-37, IL-8, and C-reactive protein might be formulated as a precise prediction model for screening severe clinical cases and have good value in clinical practice. Abstract : Early plasma interleukin 37 (IL-37) responses is correlated with benign clinical outcomes in coronavirus disease 2019, and IL-37 administration attenuates lung inflammation in human angiotensin-converting enzyme 2–transgenic mice infected with severe acute respiratory syndrome coronavirus 2.